Numerical analysis on energy-reducing and outburst-eliminating mechanism in coal mass with reaming and cavitation - Shuqing YANG; Hao ZHANG; Lei ZHANG; Wenbin HAN; Zhihui HAO; Di ZHANG; Jiamei CHANG; Zhipeng CHE; Xianji LAI (Meikuang Anquan)
Hydraulic flushing technology had been widely used in the process of gas enhanced extraction in soft coal mass. However, few studies had revealed the energy-reducing and outburst-eliminating mechanism in hydraulic flushing coal mass from the perspective of outburst potential evolution. Therefore, the numerical solution method of FLAC3D-COMSOL Multiphysics sequential coupling was used to numerically analyze the unloading damage, gas diffusion-seepage evolution and pressure relief gas migration behavior of coal mass with reaming and cavitation, the spatial and temporal evolution law of coal mass outburst potential were clarified, the energy reduction and outburst elimination characteristics of coal mass with reaming and cavitation were revealed, the influence of factors such as caving radius, caving length, cave spacing and borehole spacing on coal energy reduction and outburst elimination were also analyzed. The results show that during the process of reaming and cavitation, unloading damage occurs in the coal mass around the cave, resulting in the formation of elastic energy reduction zone, elastic energy increase zone and original elastic energy zone in the coal mass. At the same time, the gas diffusion-seepage characteristics in coal are increased by 2-3 orders of magnitude, and the gas pressure-gas expansion energy is rapidly reduced during the extraction process. In addition, with the increase of caving radius and caving length, the range of energy reduction and outburst elimination of coal mass is wider, but the energy concentration degree of elastic energy is also increasing. As the radius of the cave increases from 0.2 m to 0.8 m, the radius of the elastic energy reduction zone increases from 1.4 m to 3.5 m, the effective energy reduction radius of the gas expansion energy increases from 1.9 m to 3.7 m after 10 days of extraction, and the elastic energy concentration factor increases from 1.33 to 1.58. With the increase of the length of the cave from 0.5 m to 1.5 m, the radius of the elastic energy reduction zone increases from 1.9 m to 2.9 m, the effective energy reduction radius of the gas expansion energy increases from 2.8 m to 3.8 m after 10 days of extraction, and the elastic energy concentration coefficient increases from 1.33 to 1.46. Finally, reducing the cave spacing and borehole spacing can eliminate the increase of elastic energy between adjacent cavity, and the speed of gas expansion energy reduction is also significantly accelerated.